Revealing Religious Discrimination Experience against Indonesian Muslim Women in the United States of America - Nadiatus Salama (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2023)
Muslims in the United States (US) face religious discrimination due to an increasingly hostile environment. Further research is needed to explore the dynamics of gender differences in terms of religious discrimination as Muslim women are usually more pessimistic about their position in society compared to men. This study explores the experiences of Indonesian Muslim women in the US facing religious discrimination using qualitative methods that focus on socio-religious and psychological perspectives. In-depth interviews are conducted in Bahasa Indonesia with purposively selected respondents who are women aged 26 and above. The results demonstrate that respondents are: 1) feeling humiliated by others, 2) feeling intimidated, 3) experiencing hateful speech, and 4) experiencing religious microaggressions. This study emphasizes the need to raise awareness and promote education to combat negative stereotypes and prejudices against Muslims, particularly Muslim women, for a more inclusive and tolerant society.